FEATURES OF THE COURSE OF INFECTIVE ENDOCARDITIS IN AN ANIMAL EXPERIMENT - Rasulov Rasul Akromjon ogli; Rakhmonov Farkhod Kholbayevich; Baxriyev Ilyos Salohiddinovich (Bright Mind Publishing, 2026)
Infective endocarditis (IE) is a disease characterized by a severe course, the development of systemic complications, and an unfavorable prognosis, and it remains highly relevant in modern clinical practice. The creation of experimental models of infective endocarditis in animals makes it possible to study endothelial damage, bacteremia, vegetation formation, and the development of immune complex complications. The aim of this study was to evaluate the characteristics of the course of primary and secondary infective endocarditis in rats and rabbits using clinical-laboratory, instrumental, and pathomorphological assessments. During 2021–2022, 40 laboratory animals (20 rats and 20 rabbits) were examined under vivarium conditions. The results showed that primary infective endocarditis is more often characterized by an acute course, whereas the secondary form predominantly has a subacute course and is accompanied by immune complications (nephritis, vasculitis, synovitis). The obtained data confirm the correspondence of the experimental model with clinical observations and substantiate its significance for studying the pathogenesis of infective endocarditis and evaluating new treatment approaches.
Keywords: Infective endocarditis, experimental model, rat, rabbit, primary endocarditis, secondary endocarditis, vegetations, bacteremia, complications, nephritis, vasculitis, echocardiography.